Efetividade de uma intervenção ergonômica na postura, dor e desconforto de trabalhadores de escritório : ensaio randomizado por cluster e controlado - Barros, Fernanda Cabegi de (Universidade Federal de São Carlos, 2016)
Background: Office work is associated with prolonged awkward postures, overloading body structures when associated with improper ergonomic conditions, and may be associated with musculoskeletal disorders. Effective ergonomic interventions for reducing biomechanical exposure are not documented. Therefore it is necessary to identify effective preventive measures, using objective measurements of occupational exposure, for controlling and preventing these disorders. Objective: This study aimed to evaluate the effectiveness of an ergonomic intervention by a cluster randomized and controlled design using objective measures to evaluate head, cervical spine, thoracic spine and shoulders postures during work, perceived discomfort and musculoskeletal pain, among office workers. Methods: Sixty one administrative employees were evaluated at a university sector where 95 employees work. The allocation of subjects to the groups was performed by cluster randomization. The clusters was the rooms in which the subjects work. Thus, two groups (experimental group [EG; n = 31] and control group [CG; n = 30]) were compared before (T1) and 30 minutes (T2) after the application of the intervention. Assessment of perceived discomfort, musculoskeletal pain and postures of the head, cervical spine, thoracic spine and shoulders, and in addition, photos were taken for both groups at T1 and T2 was held. The EG received a workstation ergonomic intervention since the CG took a 15-minute break, but received no intervention in the workplace. Kolmogorov-Smirnov test were used to test the data distribution and Levene test for homogeneity of variances between groups. Then, a linear mixed model analysis was performed to compare groups at the two assessments. Mann Whitney test was applied to compare the groups for discomfort, pain and the final score of the ROSA. The data were analyzed using SPSS (version 22.0) and the significance level was set at 5%. The photos were analyzed descriptively and were also punctuated using the ROSA tool. Results: A significant interaction between group and time was found only for shoulders. The EG presented an arm lowering regarding the elevation on T2, on P90 it lowered 8,81º and 8.46, on right and left shoulders, respectively, since the CG had similar values in T1 and T2, with the P90 raising 0,88º and 1,97º on the right and left shoulders. For the upper back was found a significant difference in relation to time, showing a reduction on flexion in both groups at T2. The head and neck postures were similar between the time in both groups. On T2, the EG showed a significant reduction on perceived discomfort (2.2 mm), and pain on neck (0.07 points), shoulders (0.16 points) and upper back (0.32 points) regions; and for CG there was an increase of the same variables (0.72, 1.73, 0.82 mm and 1.06 points, respectively). Conclusion: The furniture adjustment was important to reduce the exposure of shoulders and perceived discomfort and pain referred to neck, shoulders and upper back areas. The pause was beneficial to improve superior trunk posture, probably due to postural changes. These results highlight the importance of using objective measures to evaluate the effectiveness of ergonomics interventions.
Keywords: Prevenção; Ergonomia; Inclinometria; Medidas subjetivas; Fisioterapia; Prevention; Ergonomics; Inclinometry; Subjective measures; Physiotherapy; CIENCIAS BIOLOGICAS